Neuroprotective Effects of Inositol 1,4,5-Trisphosphate Receptor C-Terminal Fragment in a Huntington's Disease Mouse Model - Tang, Tie-Shan (Society for Neuroscience, 2009)
Huntington's disease (HD) is a dominantly inherited, progressive neurodegenerative disease caused by an expanded polyglutamine tract in huntingtin protein (Htt). Medium spiny striatal neurons (MSNs) are primarily affected in HD. Mutant huntingtin protein (Htt(exp)) specifically binds to and activates type 1 inositol 1,4,5-trisphosphate receptor (InsP(3)R1), an intracellular Ca(2+) release channel. Htt(exp)–InsP(3)R1 association is mediated by a cytosolic C-terminal tail of InsP(3)R1 (a 122-aa-long IC10 fragment). To evaluate an importance of Htt(exp) association with InsP(3)R1 for HD pathology, we generated lentiviral and adeno-associated viruses expressing GFP-IC10 fusion protein and performed a series of experiments with YAC128 HD transgenic mouse. Infection with Lenti-GFP-IC10 virus stabilized Ca(2+) signaling in cultured YAC128 MSNs and protected YAC128 MSNs from glutamate-induced apoptosis. Intrastriatal injections of AAV1-GFP-IC10 significantly alleviated motor deficits and reduced MSN loss and shrinkage in YAC128 mice. Our results demonstrate an importance of InsP(3)R1–Htt(exp) association for HD pathogenesis and suggested that InsP(3)R1 is a potential therapeutic target for HD. Our data also support potential use of IC10 peptide as a novel HD therapeutic agent.